1999
DOI: 10.1116/1.591101
|View full text |Cite
|
Sign up to set email alerts
|

Dry oxidation resistance of ultrathin nitride films: Ordered and amorphous silicon nitride on Si(111)

Abstract: Articles you may be interested inFormation of ultrathin Si N x ∕ Si interface control double layer on (001) and (111) GaAs surfaces for ex situ deposition of high-k dielectrics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…2-XPS Si2p spectra for the nitride film of the control sample, N2O_1, and N2O_2. The common peak at 99.2 eV for all the three nitride films corresponds to the signal of the Si substrate, while the other peak stems from the Si-N bonding feature [10], [11]. As the number of times the N 2 O treatment increases, the peak at 102.3 eV for the control sample shifts to 103.1 eV for N2O_1 and 103.4 eV for N2O_2, which indicates that more oxygen atoms can be incorporated into the nitride film and reduced excess Si atoms and hydrogen-related species can be achieved through N 2 O annealing.…”
Section: Resultsmentioning
confidence: 98%
“…2-XPS Si2p spectra for the nitride film of the control sample, N2O_1, and N2O_2. The common peak at 99.2 eV for all the three nitride films corresponds to the signal of the Si substrate, while the other peak stems from the Si-N bonding feature [10], [11]. As the number of times the N 2 O treatment increases, the peak at 102.3 eV for the control sample shifts to 103.1 eV for N2O_1 and 103.4 eV for N2O_2, which indicates that more oxygen atoms can be incorporated into the nitride film and reduced excess Si atoms and hydrogen-related species can be achieved through N 2 O annealing.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, it is clear that the surface SiN x formed in this process was partially converted to a SiO x N y coating. Although it is well known that SiN x films can act as barriers to suppress oxidation of Si surfaces, there is a critical thickness required to protect the underlying Si . Wallace et al investigated the oxidation resistance of thin SiN x layers formed by thermal nitridation of the Si(111) surface with NH 3 .…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated that ordered and disordered SiN x films that were 0.3 and 0.2 nm thick, respectively, effectively suppressed oxidation of the underlying Si by O 2 at 600 °C. However, they noted that only an ordered Si 3 N 4 coating suppressed oxidation under atmospheric conditions . Thus, the low temperatures predicted for the Si NCs during interaction with active N‐containing species in the plasma afterglow led to a thin, disordered nitride coating that did not effectively suppress oxidation of the underlying Si NC surface.…”
Section: Resultsmentioning
confidence: 99%
“…Wallace and Wei have recently reported that very thin silicon nitride films (dϽ2 nm) have the ability to prevent oxygen from incorporating into Si͑111͒ surfaces at high temperature for an exposure to subatmospheric oxygen. 6 The ultrathin oxynitride buffer layers used in this study were also found to exhibit the high resistance to oxidation similarly. In this study, we have grown hexagonal phase of YMnO 3 ͑YMO͒.…”
Section: Introductionmentioning
confidence: 95%